Contato linguístico na fronteira Brasil/ Venezuela: produções textuais de hispanos aprendizes de PLE - Mota, Fabrício Paiva (2014)
The phenomenon of language contact is not new. Since old times, people roam the planet establishing connections with other people. In the Brazilian context, the contact between speakers of different languages is a prominent phenomenon, especially in border areas with countries of South America. Roraimense scenario, in the extreme north of Brazil, the focus of our investigation, there are two boundaries: Venezuela to the north and Guyana to the east. Given the geographical location, the state of Roraima is one of the few in the country with a trilingual border, whose official languages are Portuguese, English and Spanish. This work aims at analyzing language contact through textual productions of Venezuelans learners of Portuguese as a Foreign Language (PFL), the specific objectives are the discussion of theoretical-methodological proposals on language contact between Portuguese and Spanish, defining the types of linguistic contact presented in textual productions of Venezuelans learners of Portuguese; characterizing sociolinguistically the Venezuelan learner of Portuguese as a Foreign Language. To achieve the proposed objectives, we analyzed twenty textual productions of Venezuelans, based on the following linguistic categories, namely: Code Switching, Transfer and linguistic Interference. From a linguistic point of view, the results point to an Interactional Code Switching, concentrated on the end of the same sentence; linguistic transfer of Spelling type, in which the informant transferred orthographic structures of Spanish to Portuguese, and also interference of spelling type, in which the student omitted accent in Portuguese words and confused graphemes. From the sociolinguistic point of view, our informants are female between 20 and 54 years old, undergraduate level, live in Venezuela and have studied Portuguese for nearly 04 years for academic and professional purposes. Considering a multilingual scenario, as presented between Brazil/Venezuela, where geographical boundaries do not always correspond with the language, we conclude that the Portuguese language is occupying a privileged position in the Brazilian north end in recent years, with the inclusion of PFL course in Pacaraima as consequence of that. Among the reported phenomena of linguistic contact, Interference was the most productive in the textual productions of the students, showing the proximity between the Portuguese and Spanish.